Eksplorasi Pemahaman Santri Terhadap Konsep Moderasi Beragama dalam Kehidupan Sosial di Pondok Pesantren Tradisional - Dede Kusnadi; Asep Supriatna; Mitra Sasmita; Rahma Dilla Zainuri; Ashhabul Kahfi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
Religious moderation is an important issue in social life in the current era of globalization, especially in the Islamic boarding school environment. Al Khoir Tegalwaru Islamic Boarding School as a traditional Islamic educational institution plays a key role in forming students' attitudes of tolerance. This research aims to explore students' understanding of the concept of religious moderation in social life in Islamic boarding schools, as well as identifying the challenges faced in its implementation. The research method used is a qualitative approach with a descriptive design. Data collection was carried out through in-depth interviews with students and caregivers, as well as observations in the Islamic boarding school environment. The research results show that the majority of santri understand religious moderation as a balance between practicing religious teachings and tolerance for differences, but they face difficulties in interacting with other religious groups. Teaching of religious moderation is mostly done informally and is not well structured. Apart from that, the conservative Islamic boarding school environment also limits students' understanding of the wider application of religious moderation. The implication of this research is the need for a more systematic approach in teaching religious moderation, as well as strengthening the role of caregivers in guiding students to apply the values of moderation in everyday life. This research also provides insight for Islamic boarding school managers in improving the quality of education to be more inclusive and tolerant.Understanding santri